2011
DOI: 10.1021/cm102657v
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Strain-Induced Chemical Ordering in La0.5Sr0.5CoO3−δ Films on SrTiO3

Abstract: Fast ion conductors are at the foundation of a number of important technologies, ranging from fuel cells to batteries to gas separators. Recent results suggest that strained interfaces and thin films may offer new mechanisms for achieving enhanced ionic transport. In this work, we investigate strained 40-nm films of perovskite La0.5Sr0.5CoO3−δ, which is an important material for solid oxide fuel cell cathodes and oxygen separation membranes. We demonstrate that a strained thin film of La0.5Sr0.5CoO3−δ on SrTiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
58
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 29 publications
11
58
1
Order By: Relevance
“…Choi et al postulated such response to a decrease in the band gap in STO, which they found to occur under both compressive and tensile strains. This observation in STO is not unique, as Donner et al 113 also found the same behavior in La 0.5 Sr 0.5 CoO 3Àd as shown in Fig. 7(d).…”
Section: A Strain-effected Oxygen Vacancy Formation Energy In Bulksupporting
confidence: 75%
“…Choi et al postulated such response to a decrease in the band gap in STO, which they found to occur under both compressive and tensile strains. This observation in STO is not unique, as Donner et al 113 also found the same behavior in La 0.5 Sr 0.5 CoO 3Àd as shown in Fig. 7(d).…”
Section: A Strain-effected Oxygen Vacancy Formation Energy In Bulksupporting
confidence: 75%
“…The formation of oxygen vacancies is therefore likely to be enhanced by tensile strain in any oxide with transition metal cations with multiple oxidation states such as Mn, Fe, Co, Ni or even Cu. The coupling between strain and oxygen vacancy formation energy is moreover expected to be most pronounced in materials containing transition metal cations with localized d-electrons [45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Therefore, for the oxygen elemental state in the gas phase, we use an energy in Eq. (9) that has been corrected for such errors by comparing the calculated and experimental formation enthalpies of simple non-transition metal oxides 7 and which has been extensively tested (see for example Refs [17] - [18] and references therein). We assign the enthalpy of oxygen gas at standard state as:…”
Section: B Oxygen Gasmentioning
confidence: 99%